2014
DOI: 10.1111/hae.12465
|View full text |Cite
|
Sign up to set email alerts
|

Novel investigations on the protective role of the FVIII/VWF complex in inhibitor development

Abstract: Summary Development of inhibitory antibodies to infused factor VIII (FVIII) concentrates is the most serious unresolved complication of haemophilia A treatment. Systematic reviews suggest a twofold higher incidence of inhibitors with recombinant (rFVIII) vs. plasma‐derived (pdFVIII) FVIII products, but study methodologies vary widely. The lower immunogenicity of pdFVIII concentrates is believed to derive from the presence of von Willebrand factor (VWF) which acts as protector and chaperone for FVIII. Several n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…[22][23][24][25][26]60 In vitro and in vivo experiments showed that pdFVIII/VWF provides better protection against inhibitor neutralization than rFVIII, which results in prolonged persistence of FVIII in the circulation. 61 Most of current guidelines for ITI commonly recommend the switch for FVIII/VWF concentrates in patients who failed to achieve ITI success with rFVIII as well as for the rescue ITI. 30,31,54,62 Our study included all consecutive patients with FVIII inhibitors undergoing ITI in two HCCC and showed a high success rate in inhibitor eradication.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26]60 In vitro and in vivo experiments showed that pdFVIII/VWF provides better protection against inhibitor neutralization than rFVIII, which results in prolonged persistence of FVIII in the circulation. 61 Most of current guidelines for ITI commonly recommend the switch for FVIII/VWF concentrates in patients who failed to achieve ITI success with rFVIII as well as for the rescue ITI. 30,31,54,62 Our study included all consecutive patients with FVIII inhibitors undergoing ITI in two HCCC and showed a high success rate in inhibitor eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed explanations for this finding include the presence of Von Willebrand Factor (VWF) in pd-FVIII, reducing FVIII immunogenicity by epitope masking and prevention of endocytosis by DCs. Secondly, the different posttranslational modifications of rFVIII due to its production in mammalian cells rather than human cells might influence its immunogenicity [38][39][40][41][42]. This issue however remains highly debated, which is beyond the scope of this review.…”
Section: Lowering the Threshold Of Tolerance To Fviii Treatmentmentioning
confidence: 99%
“…Hemophilia A (HA) is an X-linked recessive bleeding disorder resulting from a quantitative or qualitative de ciency in the factor VIII (FVIII) protein [1][2][3][4][5]. Manifestation of neutralizing antibodies (inhibitors) against infused FVIII protein is the most burdensome complication of HA patients [6].…”
Section: Introductionmentioning
confidence: 99%